Transvaginal mechanotherapy for stress urinary incontinence: Principles, cellular and neuromuscular mechanisms of action, and comparison to current gold standard treatments - Alisha Fulker; Shravya Kovela; Marcus Mianulli (Continence Reports)
Mechanotransduction is a scientific principle by which cells sense and respond to mechanical stimuli. Mechanotherapy is the clinical application of mechanotransduction for tissue repair in muscle rehabilitation. Pelvic floor muscle training (PFMT) is currently the conservative gold standard of care for treatment of women with stress urinary incontinence (SUI). Mechanotherapy can increase the effectiveness of PFMT, especially when applied intravaginally for a direct transvaginal treatment to the pelvic floor muscles. With an understanding of the benefits of mechanotherapy, its mechanisms of action, and the resulting neuromuscular recruitment leading to the long-term durability of continence results, transvaginal mechanotherapy has the potential to become a complimentary first-line standard of care for women with SUI.